Bayesian optimization to design a novel x‐ray shaping device. Issue 12 (19th August 2022) - Whelan, Brendan; Trovati, Stefania; Wang, Jinghui; Fahrig, Rebecca; Maxim, Peter G; Hanuka, Adi; Shumail, Muhammad; Tantawi, Sami; Merrick, Julian; Perl, Joseph; Keall, Paul; Jr, Billy W Loo
Abstract: Purpose: In radiation therapy, x‐ray dose must be precisely sculpted to the tumor, while simultaneously avoiding surrounding organs at risk. This requires modulation of x‐ray intensity in space and/or time. Typically, this is achieved using a multi leaf collimator (MLC)—a complex mechatronic device comprising over one hundred individually powered tungsten 'leaves' that move in or out of the radiation field as required. Here, an all‐electronic x‐ray collimation concept with no moving parts is presented, termed "SPHINX": Scanning Pencil‐beam High‐speed Intensity‐modulated X‐ray source. SPHINX utilizes a spatially distributed bremsstrahlung target and collimator array in conjunction with magnetic scanning of a high energy electron beam to generate a plurality of small x‐ray "beamlets." Methods: A simulation framework was developed in Topas Monte Carlo incorporating a phase space electron source, transport through user defined magnetic fields, bremsstrahlung x‐ray production, transport through a SPHINX collimator, and dose in water. This framework was completely parametric, meaning a simulation could be built and run for any supplied geometric parameters. This functionality was coupled with Bayesian optimization to find the best parameter set based on an objective function which included terms to maximize dose rate for a user defined beamlet width while constraining inter‐channel cross talk and electron contamination. Designs for beamlet widths of 5, 7, and 10 mm 2 were generated. Each optimization was run for 300 iterations and took approximately 40 h on a 24‐core computer. For the optimized 7‐mm model, a simulation of all beamlets in water was carried out including a linear scanning magnet calibration simulation. Finally, a back‐of‐envelope dose rate formalism was developed and used to estimate dose rate under various conditions. Results: The optimized 5–, 7–, and 10‐mm models had beamlet widths of 5.1 , 7.2 , and 10.1 mm 2 and dose rates of 3574, 6351, and 10 015 Gy/C, respectively. The reduction in dose rate for smaller beamlet widths is a result of both increased collimation and source occlusion. For the simulation of all beamlets in water, the scanning magnet calibration reduced the offset between the collimator channels and beam centroids from 2.9 ±1.9 mm to 0.01 ±0.03 mm. A slight reduction in dose rate of approximately 2% per degree of scanning angle was observed. Based on a back‐of‐envelope dose rate formalism, SPHINX in conjunction with next‐generation linear accelerators has the potential to achieve substantially higher dose rates than conventional MLC‐based delivery, with delivery of an intensity modulated 100 × 100 mm 2 field achievable in 0.9 to 10.6 s depending on the beamlet widths used. Conclusions: Bayesian optimization was coupled with Monte Carlo modeling to generate SPHINX geometries for various beamlet widths. A complete Monte Carlo simulation for one of these designs was developed, including electron beam transport of all beamlets through scanning magnets, x‐ray production and collimation, and dose in water. These results demonstrate that SPHINX is a promising candidate for sculpting radiation dose with no moving parts, and has the potential to vastly improve both the speed and robustness of radiotherapy delivery. A multi‐beam SPHINX system may be a candidate for delivering magavoltage FLASH RT in humans.